Bifunctional Hydrated Gel Electrolyte for Long‐Cycling Zn‐Ion Battery with NASICON‐Type Cathode. (8th August 2021) - Lin, Xidong; Zhou, Guodong; Liu, Jiapeng; Robson, Matthew J.; Yu, Jing; Wang, Yuhao; Zhang, Zhiqi; Kwok, Stephen C. T.; Ciucci, Francesco
Abstract: Aqueous Zn‐ion batteries are promising and safe energy storage technologies. However, current aqueous electrolyte Zn‐ion battery technology is hindered by undesirable reactions between the electrolyte and electrodes, which can lead to Zn dendrite growth, gas evolution, and cathode degradation. In this study, a hydrated gel electrolyte (HGE) that combines adiponitrile (ADN) and Zn(ClO4 )2 ·6H2 O in a polymeric framework is created. ADN is found to stabilize the interface between the electrolyte and anode/cathode, enabling smooth Zn stripping/plating and reducing parasitic reactions. The HGE is simple to fabricate, inexpensive, safe, and flexible. Zn/HGE/Zn symmetrical cells can cycle more than 1000 h at 0.5 mA cm −2 and 2000 h at 0.2 mA cm −2 without short‐circuiting, indicating effective suppression of Zn dendrites. Moreover, with a NASICON‐type Sr‐doped Na3 V2 (PO4 )3 (SNVP) cathode, a Zn/HGE/SNVP full cell can be cycled over 8000 times at 10 C while retaining a high capacity of 90 mAh g −1 . Abstract : A hydrated gel electrolyte (HGE) that combines adiponitrile and Zn(ClO4 )2 ·6H2 O in a polymeric framework is created for aqueous Zn‐ion batteries. The HGE is simple to fabricate, inexpensive, stable, and flexible. With a NASICON‐type Sr‐doped Na3 V2 (PO4 )3 cathode, a full cell can be cycled over 8000 times at 10 C.